L’uso dei tempi e dei modi, traduzione delle espressioni fisse, idiomatiche e metaforiche e cambiamenti dei costrutti frasali nella versione polacca de «I dodici abati di Challant». Come superare i limiti di un sistema linguistico - Salmeri, Claudio (Studia Romanica Posnaniensia, 2013)
The purpose of this paper is to present a comparative analysis of a novel written in Italian by Laura Mancinelli, 'The Twelve Abbots of Challant', and its translation into Polish prepared by Maciej Brzozowski. Focusing on a few examples, such as the use of grammatical tenses and moods, differences in the syntax, and the problems of translating idiomatic and metaphoric expressions, the paper aims to compare the author’s style with that of the translator. The task undertaken by the translator seems very hard indeed from the very beginning due to considerable differences between the Italian and Polish languages in the use of tenses and moods. While the Italian grammar uses four moods, eight simple and seven compound tenses, the frugal Polish grammar makes with just three modes, one compound and three simple tenses. The discussion will clearly illustrate that thanks to some modifications it was possible to translate and preserve the meaning and the spirit of the Italian grammar and style.